Kontrowersje wokół instynktu macierzyńskiego wobec spadającej dzietności i aktywności seksualnej - Majcherek, Janusz A. (Studia Edukacyjne, 2024)
The decline in fertility and sexual activity in many modern countries and societies creates a new perspective for considering the controversy over the concept of maternal instinct. Extensive data shows that many young people prefer other forms of life activity than sexual and parenting. This does not mean that the maternal instinct does not exist and is merely a social construct, but it does indicate that its influence on women’s behavior is not as significant as is claimed by the proponents of the naturalized approach, who treat sexual needs and reproductive goals as the main human motivations. This means that the socio-cultural evolution produces and offers many different forms of human actualization, in the face of which the natural forms of humanity, including sexual and parental, lose their importance. Culture turns out to be stronger than nature in this respect, but in a different way than critics of paternalism, masculinism, and misogyny claim.